Evaluation Of The Anatomical Changes Of The Wrist In Normal Pregnancy By High Resolution Ultrasonography - Aziz, Mohd Ezane (2001)
Physiological changes in pregnancy can alter the anatomy of the wrist either within or outside carpal tunnel. Changes in the carpal tunnel are always related to the compression of the median nerve. The hormonal changes were thought to be a causative factor. Ultrasound using high frequency transducers offers an accurate and non invasive method for assessment of the wrist both in the normal and pathology conditions.